Organizational dynamics of interprofessional practice in the Norwegian prison system. Issue 3 (4th May 2022) - Dugdale, William; Lahtinen, Päivikki; Kajamaa, Anu; Hean, Sarah
ABSTRACT: Reoffending rates may be reduced through efforts to rehabilitate prisoners. A more nuanced understanding is needed of how front-line prison and health care services collaborate during the rehabilitation process. We report an investigation of the organizational dynamics of interprofessional practice among prison, mental health, and welfare services in two Norwegian prison case studies. First, a high security (closed) prison where a coordination network was implemented among prison management, front-line staff, and external service personnel to enhance the prisoners' life management skills. Second, an (open) transitional residence, where interprofessional practice was facilitated by front-line prison staff to increase prisoners' ability to reintegrate into society through their socialization and access to external services. The study demonstrates the demands on prisoners as they move from passive service receivers to active service users/organizer, and how interprofessional practice and models of service integration support them in this process.